Dukungan Suami dan Ibu Hamil KEK dengan Kejadian BBLR Di Wilayah Kerja Puskesmas Telaga Biru - Citra Annisa Paramita Mowu’u; Harismayanti Harismayanti; Ani Retni (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Husband support has a huge influence on wives when choosing the best course of action from pregnancy, childbirth to the post-pregnancy period so that it affects the occurrence of low birthweight. In addition, SEZ in pregnant women can cause problems not only in the mother, but also in the fetus including babies born with low birth weight. The purpose of this study was to analyze the support of husbands and SEZs in pregnant women with BBLR incidence in the working area of Telaga Biru Health Center. Quantitative research design with cross sectional approach, the population of all infants aged 0-24 months as many as 57 babies, the number of samples 57 infants using purposive sampling techniques in this study and the data were analyzed with chi-square statistical tests. The results of the study obtained that the majority of husband support was categorized as good as 46 respondents (80.7%), SEZs in pregnant women were mostly categorized as non-SEZ pregnant women as many as 44 respondents (77.2%) and the majority of BBLR events were not BBLR as many as 42 respondents (73.7%), and husband support was obtained with the incidence of BBLR p = 0.000 <α 0.05) and SEZ in pregnant women with the incidence of BBLR p = 0.000 <α 0,05. It can be concluded that there is a relationship between the support of husbands and pregnant women in SEZs with the occurrence of BBLR in the working area of the Telaga Biru Health Center.